Improvement of News Text Writing Skills Through Think Pair Share Model in VIII Grade Students of SMP Negeri 7 Rambah Samo - Arianti, Rita (FKIP-Universitas Riau, 2020)
The background of this study was due to students’ activities which do not support the achievement of learning objectives for writing news texts so that students' grades are low and do not reach the Minimal Completion Criteria (70) set at school. The purpose of this study is to improve student learning activities and outcomes in writing news texts through the application of Think Pair Share model. The type of this research is qualitative. The research method that used in this research was descriptive method. This research was conducted in 2 cycles, each cycle consisting of four stages, they are: planning, implementing, observing, and reflecting. The results of these study were (1) the quality of student activity in the pretest was 44% increased to 68% in the first cycle, and increased again in the second cycle to 90%, the quality of student learning activities increased from sufficient quality to very high quality, (2 ) an increase in mastery learning results from pretest 48.14% with an average class of 69.44 to 70.37% in the first cycle with average class of 75.19, increase in the second cycle to 100% with average class at 90,55. Based on the result of the study it can be concluded that the application of the Think Pair Share model can increase the activities and learning outcomes of grade VIII students of SMP Negeri 7 Rambah Samo in writing news texts.